People Development System for Lean Process Management Implementation - Perumal, Puvanasvaran (Penerbit UTeM, 2013)
All Original Equipment Manufacturers (OEM) organizations in Aerospace, Automotive and Electronics industries had to upgrade their functions. These organizations including suppliers and solutions providers are duty bound to improve their functions through strategic initiatives. One such initiative is Lean Process Management. Lean Process Management has proven to aid organizations in developing manufacturing and administrative management solutions and make the organization a leaner at the same time a ‘fitter’ one, achieving World Class standards in terms of production, quality, marketing, etc, etc.